Effectiveness of Reducing Ammonia Levels in Hospital Wastewater Using A Combination of Bagasse Bio Adsorbent and Nanofiltration Membrane - Laily Noor Fitri Lestari; Subriyer Nasir; Leily Nurul Komariah (Jurnal IPTEK, 2025)
The increasing environmental impact caused by hospital wastewater, particularly due to its ammonia content, necessitates innovative treatment methods. This study investigates the effectiveness of a combination of sugarcane bagasse-based activated carbon bio-adsorbent and nanofiltration membrane technology to reduce ammonia concentrations in hospital wastewater. The activated carbon was produced through carbonization at 550°C and chemical activation using 10% H2SO4. Adsorption experiments were conducted by varying bed heights (5, 7.5, and 10 cm) and flow rates (2, 3, and 4 L/min), followed by nanofiltration at 25, 30, and 35 Psi pressures. Results showed that the combined treatment reduced the wastewater pH from 9.08 to 6.53 and ammonia concentration from 4.61 mg/L to 0.02 mg/L, successfully meeting regulatory standards. This indicates that the integrated method effectively decreases ammonia levels and improves wastewater quality before discharge.